Pengaruh Good Corporate Governance Dan Reporting Lag Terhadap Kinerja Keuangan Perusahaan (Studi Empiris Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2016) - Fenny Marietza; Indah Oktari Wijayanti; Melati Agusrina (JURNAL RISET TERAPAN AKUNTANSI, 2020)
This study aims to examine the Influence of good corporate governance and reporting lag on the company's financial performance. The independent variables in this study is the mechanism of good corporate governance and reporting lag and the dependent variables is the company's financial performance as measured by the accounting ratios of return on assets (ROA), return on equity (ROE), earnings per share (EPS). The tested on each variables using a quantitative research design and secondary data are derived from companies listed on the Indonesia Stock Exchange. Data collection methods using purposive sampling in the observation period of 2012-2016, obtained 79 observations. Data were analyzed using multiple linear regression analysis. The criteria of the company used are companies that are late in reporting financial reports to the Indonesia Stock Exchange and data that support the implementation of research. The limitation of the study is that the sample of companies is limited to 79 companies and the results of heteroscedasticity test showed that the regression model was exposed to heteroscedasticity.Keywords : Good corporate governance, reporting lag